Progress of the Art of Macrophage Polarization and Different Subtypes in Mycobacterial Infection - Ge, Gai; Jiang, Haiqin; Xiong, Jingshu; Zhang, Wenyue; Shi, Ying; Tao, Chenyue; Wang, Hongsheng (Frontiers in Immunology, 2021)
Mycobacteriosis, mostly resulting from Mycobacterium tuberculosis (MTb), non-tuberculous mycobacteria (NTM) and Mycobacterium leprae (M. leprae), is the long-standing granulomatous disease that ravages several organs including skin, lung, and peripheral nerves, and it has a spectrum of clinical-pathologic features based on the interaction of bacilli and host immune response. Histiocytes in infectious granulomas mainly consist of infected and uninfected macrophages (Mφs), multinucleated giant cells (MGCs), epithelioid cells (ECs), and foam cells (FCs), which are commonly discovered in lesions in patients with mycobacteriosis. Granuloma Mφ polarization or reprogramming is the crucial appearance of the host immune response to pathogen aggression, which gets command of endocellular microbes persistence. Herein, we recapitulate the current gaps and challenges during Mφ polarization and the different subpopulations of mycobacteriosis.